Analysis of Energy Literacy and Misconceptions of Junior High Students in Taiwan - Yeh, Shin-Cheng; Huang, Jing-Yuan; Yu, Hui-Ching (Sustainability, 2017)
Decision-making regarding energy determines carbon emissions and the severity of climate change. Energy literacy plays a crucial role because well-informed citizens can support the design and implementation of smart and forward-looking policies. Research has shown that people hold misconceptions about energy, and for young students these may persist into adulthood. Thus, this study is to understand the energy literacy of junior high school students in Taiwan and what their misconceptions are as well as why and how they hold these. Energy literacy scales (ELS) were developed and served as the basis for a survey of 1652 students in five regions of Taiwan, in which most indicators for knowledge were designed corresponding to common misconceptions in the scientific and social context of energy issues. Through analyzing the survey questions and survey results, interview questions were designed and 10 students were interviewed to identify their misconceptions. A “conceptual logic map” model was developed for demonstrating the sources and patterns of misconceptions and their linkages. Potential educational strategies were then proposed, showing the applicability of the model. The combination of concept-oriented energy literacy surveys, interviews, and the conceptual logic map was proven to be an effective design for misconception identification and treatment.
Keywords: Taiwan; conceptual logic map; energy literacy; junior high school; misconception